Emansipasi pendidikan yang belum terwujud di masyarakat - Anissa, Anissa (Maliki Interdisciplinary Journal, 2026)
Education has a strategic role as an instrument of social emancipation that aims to free society from backwardness, poverty, and structural inequality. However, the reality in Indonesia shows that the emancipation of education has not been fully realized at all levels of society. This study aims to examine the factors that cause the emancipation of education to not be realized in Indonesian society and analyze the impact of these conditions on the social and economic life of the community. This study uses a descriptive qualitative approach with the method of literature study and observation of educational phenomena in the community. The results of the study show that the lack of education emancipation is influenced by various factors, including inequality of access to education due to infrastructure and geographical limitations, family socio-economic barriers, uneven quality and distribution of educators, weak implementation of education policies, and socio-cultural factors that affect public perception of the importance of education. In addition, these conditions have an impact on the inhibition of social mobility, the low quality of human resources, limited employment opportunities, increasing social inequality, and weakening of community participation in social and democratic life. Thus, this study emphasizes that educational emancipation has not been substantively realized and requires more inclusive, contextual, and equitable policy efforts so that education can truly function as a means of community empowerment.